Czy ksiądz Piotr Skarga wdawał się w politykę? Wokół sporu o polityczne zaangażowanie ks. Piotra Skargi SI - Bruździński, Andrzej (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
One of the many complaints directed against the Jesuit Father Piotr Skarga (1536–1612),the preacher of the Polish King Sigismund III Vasa (1566–1632) was the accusation of meddling in politics. During the period of seditions and religious squabbles of Polish nobility of that time he was even described as „praecipuus turbator Reipublicae” (Chief Disturber of the Republic). In response to these accusations the ambivalence of the term “politics” must be emphasised. According to the classic definition, politics is a sagacious care about the common good. According to one of the modern definitions, however, by Max Weber, it is a deprived-of-ethics drive to take over and retain power. In the classic understanding of politics, all actions by Father Skarga, be it in the field of preaching, charity or education were politically tinted. In the modern understanding, however, they cannot be perceived as political but at the most, pre-political, that is aimed at shaping the political attitudes of the society which Skarga formed through his preaching and social actions.